Decompression illness secondary to occupational diving : recommended management based current legistation and practice in Malaysia. - Ahmad, Rozali; H., Khairuddin; Mohd Sidik, Sherina; B., Mohd Zin; A., Sulaiman (Malaysian Medical Association, 2008)
Occupational divers are exposed to hazards which contribute to the risk of developing decompression illnesses (DCI). DCI consists of Type I decompression sickness (DCS), Type II DCS and arterial gas embolism (AGE), developed from formation of bubbles in the tissues or circulation as a result of inadequate elimination of inert gas (nitrogen) after a dive. In Malaysia, DCI is one of the significant contributions to mortality and permanent residual morbidity in diving accidents. This is a case of a diver who suffered from Type II DCS with neurological complications due to an occupational diving activity. This article mentions the clinical management of the case and makes several recommendations based on current legislations and practise implemented in Malaysia in order to educate medical and health practitioners on the current management of DCI from the occupational perspective. By following these recommendations, hopefully diving accidents mainly DCI and its sequalae among occupational divers can be minimized and prevented, while divers who become injured receive the proper compensation for their disabilities.